Trimethylamine N-Oxide in Heart Failure: A Meta-Analysis of Prognostic Value - Li, Xingxing; Fan, Zongjing; Cui, Jie; Li, Dong; Lu, Jinjin; Cui, Xiaoyun; Xie, Liandi; Wu, Yang; Lin, Qian; Li, Yan (Frontiers in Cardiovascular Medicine, 2022)
Objective: The present study aimed to explore the prognostic value of TMAO in HF. Methods: PubMed, Excerpta Medica Database (EMBASE), Cochrane Library, Web of Science, Wanfang Database, SINOMED, China Science and Technology Journal Database (VIP) and China National Knowledge Infrastructure (CNKI) were searched up to June 1, 2021. Studies recording the major adverse cardiovascular events (MACEs) or all-cause mortality in HF patients and their circulating TMAO concentrations were included. Meta-analysis was performed using Stata 13.0. Results: Ten articles (12 studies) involving 13425 participants from 2014 to 2021 were considered. Compared to low-level TMAO, elevated TMAO was correlated with MACEs and all-cause mortality in HF (RR: 1.28, 95% CI: 1.17, 1.39, P < 0.0001, random effects model and RR: 1.35, 95% CI: 1.28, 1.42, P < 0.0001, random effects model, respectively). Consistent results were obtained in all examined subgroups as well as in the sensitivity analysis. Conclusion: Elevated TMAO may be an adverse prognostic indicator in patients with HF.